TINGKAT KECEMASAN PADA PASIEN ANAK USIA SEKOLAH (6-12 TAHUN) DI RUANG IGD RSUD MAJALAYA KABUPATEN BANDUNG: ANXIETY LEVEL IN SCHOOL-AGE PATIENTS (6-12 YEARS) IN THE EMERGENCY ROOM AT MAJALAYA REGIONAL HOSPITAL BANDUNG REGENCY - PRAGHOLAPATI, ANDRIA; Sarinengsih, Yuyun; Susilawati, . (Bali Medika Jurnal, 2019)
Anxiety arises because the child can not do what he wants and can only lie in bed. One of children's anxiety that occurs due to injuries to the body such as infusion and wound care. The effects of child anxiety on nurses include prolonged treatment and infusion often released because the child continues to rebel. The purpose of this study was to describe the level of anxiety in school-age children (6-12 years) in the emergency room at Majalaya Regional Hospital Bandung Regency 2017. The design of the study was a descriptive study, with a purposive sampling sample collection technique. Data collection was done by means of observation to respondents. Data was presented in the form of frequency distribution, with a sample of 93 people. Based on the results of the study note that anxiety in school-age child patients (6-12 years) in the emergency room Majalaya Regional Hospital Bandung regency mostly experienced anxiety as many as 72 people (77.4%) and a small proportion did not experience anxiety as many as 21 people (22.6 %). Conclusions are found that the majority of school-age pediatric patients experience anxiety. Suggestions for nurses to be able to deal with all problems faced by patients and patients' families such as nurses are able to conduct therapeutic communication to calm patients.